2021
DOI: 10.18488/journal.31.2021.81.48.56
|View full text |Cite
|
Sign up to set email alerts
|

Preferred Social Networking App by Employees in Tourism and Hospitality Industry in Kenya

Abstract: The purpose of this paper was to examine the preferred social media application network by employees in the tourism and hospitality industry. The specific aims were to examine the preferred social media amongst Facebook, WhatsApp, Twitter, Instagram, LinkedIn, email and YouTube, examine the relationship between respondent's gender, a position at workplace and choice of social media and finally find out official the duties performed by the respondent's using the smartphones. The finding indicated that the most … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…From the perspective of travel booking, relevant scholars point out the role of network information technology in online travel booking, and through the study of the development trend of online travel booking, it is concluded that there will be a series of changes in online travel booking, which is the basis for the further exploration of travel e-commerce [10]. e development space provides development ideas and promotes new breakthroughs and progress in the tourism industry.…”
Section: Related Workmentioning
confidence: 99%
“…From the perspective of travel booking, relevant scholars point out the role of network information technology in online travel booking, and through the study of the development trend of online travel booking, it is concluded that there will be a series of changes in online travel booking, which is the basis for the further exploration of travel e-commerce [10]. e development space provides development ideas and promotes new breakthroughs and progress in the tourism industry.…”
Section: Related Workmentioning
confidence: 99%